Time-motion analysis of small-sided training games and competition in elite women soccer players - Gabbett, T. J.; Mulvey, M. J. (The Journal of Strength and Conditioning Research, 2008)
We investigated the movement patterns of small-sided training games and compared these movement patterns with domestic, national, and international standard competition in elite women soccer players. In addition, we investigated the repeated-sprint demands of women's soccer with respect to the duration of sprints, number of sprint repetitions, recovery duration, and recovery intensity. Thirteen elite women soccer players [age (mean ± SD) 21 ± 2 years] participated in this study. Time-motion analysis was completed during training (n = 39) consisting of small-sided (i.e., three versus three and five versus five) training games, domestic matches against male youth teams (n = 10), Australian national-league matches (n = 9), and international matches (n = 12). A repeated-sprint bout was defined as a minimum of three sprints, with recovery of less than 21 seconds between sprints. The overall exercise to rest ratios for small-sided training games (1:13) were similar to or greater than domestic competition against male youth teams (1:15) and national-league (1:16) and international (1:12) competitions. During the international matches analyzed, 4.8 ± 2.8 repeated-sprint bouts occurred per player, per match. The number of sprints within the repeated-sprint bouts was 3.4 ± 0.8. The sprint duration was 2.1 ± 0.7 seconds, and the recovery time between sprints was 5.8 ± 4.0 seconds. Most recovery between sprints was active in nature (92.6%). In contrast to international competition, repeated-sprint bouts were uncommon in small-sided training games, domestic competition against male youth teams, and national-league competition. These findings demonstrate that small-sided training games simulate the overall movement patterns of women's soccer competition but offer an insufficient training stimulus to simulate the high-intensity, repeated-sprint demands of international competition.